Interest Rate Seasonals and the Federal Reserve - Clark, Truman A. (Journal of Political Economy, 1986)
It is widely believed that one of the Federal Reserve's first important monetary policy achievements was the deseasonalization of interest rates. The Federal Reserve supposedly accomplished this by introducing appropriate seasonal movements into the supplies of currency and high-powered money. This view implicitly assumes that there was no interaction between American and foreign financial markets. Two findings are reported that challenge this conventional view. First, interest rate seasonals disappeared in the United States and other countries at approximately the same time. Second, interest rate seasonal ended approximately 3 years before the seasonal movements of currency and high-powered money changed.